Analysis of rare genetic variants in All of Us cohort patients with common variable immunodeficiency - von Beck, Troy; Patel, Meera; Patel, Niraj C.; Jacob, Joshy (Frontiers in Genetics, 2024)
Common variable immunodeficiency (CVID) is a group of genetic disorders involving more than a dozen genetic loci and characterized by a deficiency in specific antibody isotypes leading to poor immune responses and recurrent infection. CVID affects approximately 1 in 10,000 to 1 in 50,000 people worldwide with substantial heterogeneity in disease severity, including asymptomatic individuals designated as hypogammaglobulinemia of undetermined significance (HGUS). As expected of humoral immunodeficiency, the molecular causes of CVID primarily affect the maturation, activation, or survival of B cells and plasma cells. In this retrospective analysis, we defined a cohort of 21 patients with a primary CVID or HGUS diagnosis in the v7 release of the All of Us Research Program database and performed gene annotation and variant effect prediction. Our analysis identified both known disease-causing variants and rare genetic variants overlapping with other immunodeficiency syndromes.